The icky bug alphabet book - Pallotta, Jerry; Masiello, Ralph (Watertown, MA : Charlesbridge, 1986)
Introduces the characteristics and activities of insects and other crawly creatures from A to Z, beginning with the ant and concluding with the zebra butterfly.
4.9
K-3
Keywords: English language -- Alphabet -- Juvenile literature; Insects -- Juvenile literature; Alphabet; Insects; Alphabet; Insects